"Are Ye Able?" The Methodist Youth Department, Racial Justice, and Church Reform in Mid-Twentieth Century America. Issue 2 (November 2014) - Bergler, Thomas E.
Between 1930 and 1970, national Methodist youth leaders led a sustained liberal religious education campaign to mobilize young Methodists for racial justice. Ironically, by promising too much, liberal religious education theorists influenced Methodist youth leaders and young people to see themselves as failures, despite their many impressive successes. Their story further suggests that it was not just the rise of new intellectual movements or Christian education theories, but also disillusionment with the results produced by liberal religious education methods that drove changes in 20th-century Christian education.